2018
DOI: 10.3846/jbem.2018.1480
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Money on Output in Czech Republic and Romania

Abstract: Abstract. The problem of relationship between output and money has become again a subject of special interests of economists after the most recent global financial crisis and monetary stabilization policies applied by central banks of almost all developed economies. In this context, the main aim of this paper is to assess the relation between GDP and the most important monetary variables in two countries: Romania and Czech Republic over the period of 1995:Q1 -2015:Q4. The choice of these economies was delibera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…The result shows that in the long-run, a 1% increase in money supply will be accompanied by a 7.9% rise in the GDP level, assuming all things remain the same, while in the short-run, a 1% raise in money supply will lead to 5.7% increase in GDP. This supports the findings of Simionescu et al (2018), which was obtained for chosen Central European countries, and Waheed and Younus (2010), though they found significant impact of the ratio of M2 to GDP on economic growth. The reason for the insignificant result of this study is that, the ratio of M2 to GDP measures the extent of monetization rather than financial depth in developing countries (Demetriades & Luintel, 1996;Luintel & Khan, 1999).…”
Section: 000supporting
confidence: 90%
“…The result shows that in the long-run, a 1% increase in money supply will be accompanied by a 7.9% rise in the GDP level, assuming all things remain the same, while in the short-run, a 1% raise in money supply will lead to 5.7% increase in GDP. This supports the findings of Simionescu et al (2018), which was obtained for chosen Central European countries, and Waheed and Younus (2010), though they found significant impact of the ratio of M2 to GDP on economic growth. The reason for the insignificant result of this study is that, the ratio of M2 to GDP measures the extent of monetization rather than financial depth in developing countries (Demetriades & Luintel, 1996;Luintel & Khan, 1999).…”
Section: 000supporting
confidence: 90%
“…The money neutrality hypothesis is rejected not only in advanced economies. Simionescu, Balcerzak, Bilan, and Kotásková (2018) find a cointegration between M3, GDP and internal credit in the two following post-transformation Central European economies: Romania and the Czech Republic. Similarly, Osińska, T. Kufel, Błażejowski, and P. Kufel, (2018) identify a considerable role played by the monetary mechanism in diagnosing the phases of a business cycle in most of the European economies.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Bonini and Alkan (2012) concluded that there was a statistically significant negative relationship between the level of interest rates and the volume of VC investments. Rising interest rates reduce the supply of capital as investors move part of their resources to assets with the risk-free interest rate (Janus, 2019;Simionescu et al, 2018). On the other hand, the growth of interest rates can paradoxically contribute to the development of alternative financing sources, including the risk capital market, due to the increase in debt capital costs (Chodnicka-Jaworska & Jaworski, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%